Patient Perspectives on EMS Alternate Destination Models. (1st November 2016) - Munjal, Kevin G.; Shastry, Siri; Loo, George T.; Reid, Daniel; Grudzen, Corita; Shah, Manish N.; Chapin, Hugh H.; First, Brandon; Sirirungruang, Sasilada; Alpert, Erin; Chason, Kevin; Richardson, Lynne D.
Abstract: Introduction: Studies have shown that a large number of ambulance transports to emergency departments (ED) could have been safely treated in an alternative environment, prompting interest in the development of more patient-centered models for prehospital care. We examined patient attitudes, perspectives, and agreement/comfort with alternate destinations and other proposed innovations in Emergency Medical Services (EMS) care delivery and determined whether demographic, socioeconomic, acuity, and EMS utilization history factors impact levels of agreement.Methods: We conducted a cross-sectional study on a convenience sample of patients and caregivers presenting to an urban academic ED between July 2012 and May 2013. Respondents were surveyed on levels of agreement with 13 statements corresponding to various aspects of a proposed patient-centered emergency response system including increased EMS access to healthcare records, shared decision making with the patient and/or primary care physician, transport to alternative destinations, and relative importance of EMS assessment versus transportation. Information on demographic and socioeconomic factors, level of acuity, and EMS utilization history were also determined via survey and chart review. Responses were analyzed descriptively and compared across patient characteristics using chi-square and regression analyses.Results: A total of 621 patients were enrolled. The percentage of patients who agreed or strongly agreed with each of the 13 statements ranged from 48.2 to 93.8%. About 86% agreed with increased EMS access to healthcare records; approximately 72% agreed with coordinating disposition decisions with a primary physician; and about 58% supported transport to alternative destinations for low acuity conditions. No association was found between levels of agreement and the patient's level of acuity or EMS utilization history. Only Black or Hispanic race showed isolated associations with lower rates of agreement with some aspects of an innovative EMS care delivery model.Conclusion: A substantial proportion of patients surveyed in this cross sectional study agreed with a more patient-centered approach to prehospital care where a 9-1-1 call could be met with a variety of treatment and transportation options. Agreement was relatively consistent among a diverse group of patients with varying demographics, levels of acuity and EMS utilization history.MeSH Key words: emergency medical services; triage; telemedicine; surveys and questionnaires; transportation of patients